GROWTH OF LISTERIA MONOCYTOGENES IN DEFINED MEDIA - Friedman, Mischa E. (1961)
Friedman, Mischa E. (U. S. Army Chemical Corps, Fort Detrick, Frederick, Md.), and William G. Roessler. Growth of Listeria monocytogenes in defined media. J. Bacteriol. 82:528–533. 1961—Listeria monocytogenes, strains A4413, JHH, and 9037-7, require organic sulfur, valine, and isoleucine for growth. In addition, A4413 requires leucine, whereas 9037-7 requires leucine, histidine, and arginine. Glutamine is stimulatory for all three strains. Further, A4413 is stimulated also by histidine, arginine, and methionine, and JHH by histidine, arginine, and leucine. With A4413, glutamine can be replaced by inorganic ammonium salts, urea, or asparagine but not by glutamic acid. Growth inhibition by d-serine is reversed by glycine or alanine. Growth with agitation in defined media is very poor and subculture is not possible unless unidentified products of enzymatic hydrolysis of proteins are present. A requirement for lipoic acid was not observed with five strains of L. monocytogenes.